Crystal structure and Hirshfeld surface analysis of the elusive trichlorobis(diethyl ether)oxomolybdenum(V). Issue 10 (19th September 2020) - Shaw, Thomas E.; LeMagueres, Pierre; Sattelberger, Alfred P.; Jurca, Titel
Abstract : Structural confirmation of the elusive mer ‐MoCl3 O(Et2 O)2 complex has been achieved through single‐crystal X‐ray diffraction techniques and Hirshfeld surface analysis. Abstract : First reported in 1930, MoCl3 O(Et2 O)2 is a by‐product of the reductive synthesis of MoCl4 (OEt2 )2 from MoCl5 . We report herein the X‐ray crystal structure and Hirshfeld surface characteristics of mer ‐MoCl3 O(Et2 O)2, or [MoCl3 O(C4 H10 O)2 ]. The compound crystallizes in the orthorhombic space group P 21 21 21 . The molybdenyl (Mo=O) bond length is 1.694 (3) Å and the cis ‐ and trans ‐Mo—O distances are 2.157 (3) and 2.304 (3) Å, respectively. Intermolecular Mo=O…H bonding is present in the lattice, with the shortest distance being 2.572 Å.